CONTROL THE BODY TEMPERATURE OF LED LAMPS AT WORK IN DIFFERENT LIGHTING DEVICES - Aihaiti Yisihakefu; R. H. Tukshaitov (Известия высших учебных заведений: Проблемы энергетики)
The temperature of the housing of LED lamps is determined under different conditions of their operation in lighting devices. It is shown that the creation of ventilation holes in the plafond or in the system of its fastening allows to lower the body temperature of LED lamps by 1025% and thereby significantly increase the service life.